Peningkatan Hasil Belajar Keseimbangan Melalui Modifikasi Balok Titian Bertingkat Baris Kepemilikan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The goal of this research is to improve learning outcomes through the modification of the balance beam bridge multilevel media in the third-grade students of SD Negeri Pegirikan 01 Sub Gutters Kabupaten Tegal 2013/2014 school year.Teknik the data and data collection instruments used in the form of student assessment test with a rubric that includes three domains, namely cognitive, affective and psychomotor, then a non-test in the form of question and answer techniques with students and observations for information about the cognitive, affective, psychomotor. The research instrument used syllabi, lesson plans, observation sheets, and tests. Data analysis using quantitative data analysis and data analysis research qualitative.Prosedur consists of planning, implementation, observation, and reflection.Based on the results of the study showed indications of improvement of the learning process based on observations of the assessment sheet penjasorkes experts and teachers, and a list of student scores showed a good response. Cycle 1 showed 72.7% of students pass the study while the second cycle increased to 95.5% thus be advisable.With penjasorkes learning through media-rise bridge beams can be used as an alternative to improve the learning process so that students can increase learning outcomes.